The making of the Black working class in Britain - Ramdin, Ron (London, 2017)
"This is the first comprehensive historical perspective on the relationship between black workers and the changing patterns of Britain's labour needs. It places in an historical context the development of a small black presence in sixteenth-century Britain into the disadvantaged black working class of the 1980s. The book deals with the colonial labour institutions (slavery, indentureship and trade unionism) and the ideology underlying them and also considers the previously neglected role of the nineteenth-century black radicals in British working class struggles. Finally, the book examines the emergence of a black radical ideology that has underpinned the twentieth-century struggles against unemployment, racial attacks and workplace grievances, among them employer and trade union racism."